PENGARUH KUALITAS LABA TERHADAP NILAI PERUSAHAAN - Siallagan, Hamonangan (Jurnal Akuntansi Kontemporer, 2009)
The purpose of this research is to investigate and give empirical evidence of the effect of earnings quality onfirm value. The proposed hypotheses is earnings quality positively influence value of the firm. To test alternative hypotheses, this research used manufacturing listed on Jakarta Exchange Stock which issue financial statement. PW]Josive sampling is usedfor data collection with 74 manufacturing sample and observation sum 197. The result indicales that earnings quality influence the value of the firm. The earnings quality of pro x)' stated by Sloan (1996), Chan et al. (2001) and Warfield et al. (1995) is discretionary accruals.